2017
DOI: 10.1111/jnc.14229
|View full text |Cite
|
Sign up to set email alerts
|

Screening the expression characteristics of several miRNAs in G93A‐SOD1 transgenic mouse: altered expression of miRNA‐124 is associated with astrocyte differentiation by targeting Sox2 and Sox9

Abstract: MicroRNAs (miRNAs) are suspected to be a contributing factor in amyotrophic lateral sclerosis (ALS). Here, we assess the altered expression of miRNAs and the effects of miR-124 in astrocytic differentiation in neural stem cells of ALS transgenic mice. Differentially expressed miRNA-positive cells (including miR-124, miR-181a, miR-22, miR-26b, miR-34a, miR-146a, miR-219, miR-21, miR-200a, and miR-320) were detected by in situ hybridization and qRT-PCR in the spinal cord and the brainstem. Our results demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 54 publications
2
41
1
Order By: Relevance
“…Moreover, overexpression of miR‐124 induces neuron‐specific differentiation by increasing β ‐III tubulin expression and decreasing GFAP expression (Jiao, Liu, Yao, & Teng, ). In contrast to our study, Zhou et al have shown that miR‐124 may regulate astrocyte differentiation by targeting Sox2 and Sox9 in amyotrophic lateral sclerosis transgenic mice (Zhou et al, ). Other miRNAs, such as miR‐145 , miR‐495 , and miR‐101 , are consistently downregulate the expression of Sox9 3′‐UTR reporter genes (Lee et al, ; Yang et al, ; Zhang et al, ).…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, overexpression of miR‐124 induces neuron‐specific differentiation by increasing β ‐III tubulin expression and decreasing GFAP expression (Jiao, Liu, Yao, & Teng, ). In contrast to our study, Zhou et al have shown that miR‐124 may regulate astrocyte differentiation by targeting Sox2 and Sox9 in amyotrophic lateral sclerosis transgenic mice (Zhou et al, ). Other miRNAs, such as miR‐145 , miR‐495 , and miR‐101 , are consistently downregulate the expression of Sox9 3′‐UTR reporter genes (Lee et al, ; Yang et al, ; Zhang et al, ).…”
Section: Discussioncontrasting
confidence: 99%
“…Among other miRNAs suspected to contribute to ALS pathology is the altered expression of miR-146a and miR-21in the SC and brainstem of ALS transgenic mice [81]. Similarly to these authors we also found reduced miR-146a levels in the cortical homogenates, a feature not observed in the SC from the same mSOD1 mice model, in either stage 1 or stage 2 [19].…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the elevated levels seem to be negatively correlated with the STAT3 transcription factor, a key factor for neural differentiation and cell survival (Marcuzzo et al, 2014). In a study of neural stem cells from ALS transgenic mice, Zhou et al (2018) showed that miR-124 was downregulated in the brainstem and spinal cord, and that miR-124 may participate in astrocyte differentiation of ALS transgenic mice by targeting Sox2 and Sox9. Many studies have reported that the expression level of miR-124 is inconsistent in ALS models, which may be related to the samples selected by different studies, and more studies in the future may draw more clear conclusions.…”
Section: Mir-124 In Neurodegenerative Disordersmentioning
confidence: 99%